2003
DOI: 10.1046/j.1440-1711.2003.01193.x
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of CD4+ and CD8+ T cells during experimental infection with Mycobacterium avium is controlled by Fas/FasL and Bcl‐2‐sensitive pathways, respectively

Abstract: Summary Both CD4 + and CD8 + T cells from mice infected with Mycobacterium avium suffered a high rate of apoptosis, beginning with the onset of the immune response and culminating in the loss of T cells from the tissues and loss of IFN-γ production. Fas expression increased over the course of infection on both T cell populations, as did their susceptibility to the induction of apoptosis in vitro by anti-Fas mAb. Nevertheless, although the rate of apoptosis among CD4 + T cells from infected mice was reduced to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 42 publications
0
20
1
Order By: Relevance
“…There remain other possible candidates that should be investigated for their participation in this process of T-cell elimination, such as the receptors for TNF-related apoptosisinducing ligand. These data contrast with recent results reported by Zhong et al (38), who showed that apoptosis of CD4 ϩ T cells during infection by M. avium was dependent on CD95/Fas and that of CD8 ϩ T cells was prevented by overexpression of Bcl-2. The course of infection studied by the latter group is however distinct from the one we studied.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…There remain other possible candidates that should be investigated for their participation in this process of T-cell elimination, such as the receptors for TNF-related apoptosisinducing ligand. These data contrast with recent results reported by Zhong et al (38), who showed that apoptosis of CD4 ϩ T cells during infection by M. avium was dependent on CD95/Fas and that of CD8 ϩ T cells was prevented by overexpression of Bcl-2. The course of infection studied by the latter group is however distinct from the one we studied.…”
Section: Discussioncontrasting
confidence: 99%
“…In the latter studies, such T-cell loss was observed at different sites of infection and was explained by the increase in apoptosis of T cells in infected animals (14). More recently, it was shown to be mediated by CD95 in CD4 ϩ T cells and prevented by Bcl-2 in CD8 ϩ T cells (38). T-cell loss was also described during Mycobacterium bovis BCG infection by Dalton and coworkers (5).…”
mentioning
confidence: 94%
“…However the exact nature of the role played by PE genes in providing survival benefits to macrophages harboring M. tuberculosis from surrounding T cells in granulomas or during pathogenesis associated with infection remains unclear. It has been reported that many antigens including PPD antigen of M. tuberculosis bacilli interact with T cells during antigen presentation and induce apoptosis in reactive human T cells [6,17,18]. Furthermore, M. avium promotes CD8 T cell apoptosis upon exposure to macrophages in mice infection model [19].…”
Section: Introductionmentioning
confidence: 99%
“…avium can also cause the apoptotic death of cell types besides monocytes and macrophages, including dendritic cells [91] and T cells [97,98]. Apoptosis of CD4 + and CD8 + T cells occurs via different pathways, with CD4 + T cells dying via Fas/FasL interactions, and CD8 + cells undergoing apoptosis via the intrinsic pathway, which can be prevented by overexpression of Bcl-2 [98]. Induced death of these immune effector cells may contribute to bacterial persistence.…”
Section: Mycobacterium Aviummentioning
confidence: 99%